Waringin Sehat: Program Edukasi, Pencegahan, dan Akses Kesehatan Untuk Hidup Lebih Baik - Yus Alvar Saabighoot; Yusrafidin Yusrafidin; Rakhmini Juwita; Rizka Nurhalija; Rory Fitriani Larasati; Annisa Raudhatul Jannah; Lulu Ilmanunah (Unri Conference Series: Community Engagement, 2025)
The problem of stunting and malnutrition in early childhood remains a serious challenge in Indonesia. Data shows a high prevalence of stunting, necessitating integrated and sustainable interventions. The "Waringin Sehat" Pengabdian Kepada Masyarakat (PkM) Program aims to improve the knowledge of parents and early childhood education educators about balanced nutrition and strengthen family food security. Methods: This program adopts a community empowerment approach based on education, participatory training, and active mentoring. Its implementation involves close collaboration between the PkM team, parents, Ibnu Umbara Early Childhood Education educators, and village officials. The program is implemented through five stages: (1) preparation and mapping of needs, (2) intervention planning, (3) implementation of education and training activities, (4) monitoring and evaluation, and (5) reflection and sustainability strategies. Results: This program successfully improved parents' understanding of balanced nutrition and stunting prevention. The training provided to early childhood educators equipped them with the skills to integrate nutrition materials into the curriculum. The program also successfully formed active community learning groups and encouraged the use of local food through simple urban farming initiatives. The resulting outputs include modules, guidebooks, educational videos, and teaching aids. Conclusion: "Waringin Sehat" has made a significant positive contribution, creating positive behavioral changes and fostering community independence in addressing nutritional issues. This success confirms that integrated and participatory interventions are highly effective in achieving sustainable impact.